1987
DOI: 10.1007/bf00149945
|View full text |Cite
|
Sign up to set email alerts
|

C-wave versus electrooculogram in diseases of the retinal pigment epithelium

Abstract: The c-wave and the electrooculogram (EOG) are retinal potentials predominantly generated by the pigment epithelium. In most diseases both parameters show a parallel decrease in amplitude. However, in patients with dominant drusen, and cone dystrophies, and in clinically nonaffected members of families suffering from vitelliform macula degeneration, the EOG is close to normal whereas the c-wave shows a reduced amplitude. These findings suggest a higher sensitivity of the generators of the c-wave compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The small drusen seen in our patients are thin, uniform in size, and radially aligned to the fovea whereas so 49,[55][56][57] Genetic testing of patients with cuticular or basal laminar drusen for the EFEMP1 mutation should help to determine the relationship between this disorder and ML/DHRD. There are conflicting reports regarding the functional attributes of various dominantly-inherited drusen syndromes with respect to the ERG and EOG, [4][5][6]8,15,41,46,47,56,[58][59][60][61][62][63] colour vision, 4,8,11,44,58,64 and dark adaptation. 4,6,8,41,44,46,58,63,65 This disparity in findings may be related to several factors that include the definition of inherited vs age-related drusen, 61,62 the sensitivity of the tests employed, the stage of the disease, or whether they represent the same or different disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The small drusen seen in our patients are thin, uniform in size, and radially aligned to the fovea whereas so 49,[55][56][57] Genetic testing of patients with cuticular or basal laminar drusen for the EFEMP1 mutation should help to determine the relationship between this disorder and ML/DHRD. There are conflicting reports regarding the functional attributes of various dominantly-inherited drusen syndromes with respect to the ERG and EOG, [4][5][6]8,15,41,46,47,56,[58][59][60][61][62][63] colour vision, 4,8,11,44,58,64 and dark adaptation. 4,6,8,41,44,46,58,63,65 This disparity in findings may be related to several factors that include the definition of inherited vs age-related drusen, 61,62 the sensitivity of the tests employed, the stage of the disease, or whether they represent the same or different disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The results from electro-oculograms (EOGs), non-photic EOGs, electroretinograms (ERGs), pattern electroretinograms (PERGs), and multifocal ERGs are controversial. [13][14][15][16][17][18][19][20][21][22][23] Psychophysically determined losses of rod sensitivity have been reported to occur before other symptoms. [24][25][26] Slight losses of visual acuity occur in patients with large soft drusen, and there may be slight and various changes with Amsler chart.…”
mentioning
confidence: 99%
“…In this way, the work of many authors was considerable [3-6, 8, 14, 15], In the last 6 years the clinical evaluation of C waves in various fundus diseases showed that the C wave reflects the function of the retinal pigment epithelium about equally. maybe sometimes with a higher sensitivity than the electrooculogram [9][10][11].…”
Section: Introductionmentioning
confidence: 99%